Revisiting Sustainable Tourism Practices in ASEAN Member State: A Study on the Saba Baduy in Indonesia - Santoso, Tulus; Nurasa, Heru; Rusli, Budiman; Sumadinata, R. Widya Setiabudi (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2025)
Being brought in as a tool to empower socio-cultural integration between Southeast Asian countries, the ASEAN Tourism Strategy Plan (ATSP) has become a standard norm among Southeast Asian countries to achieve sustainable tourism practices. Discussing local tourism policy prospects for regional integration is central to understanding whether compliance with ATSP standards, which is notably regarded as a non-sensitive issue in the ASEAN socio-cultural pillar, is applicable at the regional level, and beneficial for the local authorities. Despite that ASEAN countries have strongly relied on the tourism economy, scholars have yet to understand whether member states are ready to comply with ATSP. This research aimed to thoroughly evaluate sustainable tourism development in one destination site in Indonesia, using the case study of Saba Budaya Baduy of Banten Province. By reviewing policy measures, aspirations and interests of diverse actors in Banten, the research argued that adherence to ATSP is constrained by the dilemma between promoting economic development and preserving the cultural heritage of the Baduy Indigenous people. The research applied a qualitative method with a case study approach, which involves in-depth interviews, field observations, and analysis of policy documents. It also suggests that to ensure the readiness to comply with ATSP, the Indonesian authority needs more participatory policies.